The outlook of building information modeling for sustainable development - Chong, Heap Yih; Wang, X. (2016)
As human needs evolve, information technologies and natural environments require a wider perspective of sustainable development, especially when examining the built environment that impacts the central of social-ecological systems. The objectives of the paper are (a) to review the status and development of building information modeling (BIM) in regards to the sustainable development in the built environment, and (b) to develop a future outlook framework that promotes BIM in sustainable development. Seven areas of sustainability were classified to analyze forty-four BIM guidelines and standards. This review examines the use of BIM in sustainable development, focusing primarily on certain areas of sustainability, such as project development, design, and construction. The developed framework describes the need for collaboration with the multiple disciplines for the future adoption and use of BIM for the sustainable development. It also considers the integration between “BIM and green assessment criteria”; and “BIM and renewable energy” to address the shortcomings of the standards and guidelines.